Atypical adverse events in a real-world study of long-term immunomodulation for multiple sclerosis and neuromyelitis optica spectrum disorder - Amelie Kirschbaum; Felix Luessi; Arda Civelek; Stefan Bittner; Johannes Piepgras; Frauke Zipp (Therapeutic Advances in Neurological Disorders)
Background: Immunotherapies are integral in managing multiple sclerosis (MS) and related demyelinating diseases, but adverse drug reactions significantly affect the tolerability of disease-modifying therapies (DMTs). Objectives: This study aims to assess the safety profile of DMTs within a real-world cohort affected by MS and related diseases and to identify atypical adverse events (AEs) and those of exceptional severity. Methods: A retrospective analysis was conducted on 3850 patients with MS, neuromyelitis optica spectrum disorder (NMOSD), and related conditions (2009–2022). Demographic and clinical data were analyzed for patients treated with DMTs. Parameters included prior treatments, AEs, treatment durations, and reasons for discontinuation. Results: Of the cohort, 1989 patients (71.1% female) with a median follow-up of 46.3 months during DMT use were included. Monotherapy was employed in 987 patients, while 1002 received sequential DMTs, totaling 3850 treatments. Adverse reactions led to discontinuation in 24.2% of cases, while disease progression accounted for 22.9%. Among 1878 AEs, 31 (1.7%) were atypical, and 59 (3.1%) were unusually severe, which was systematically categorized based on type, timing, and remission. Conclusion: Within the confines of this real-world study, DMT administration emerged as generally well tolerated in MS, related demyelinating diseases and NMOSD. The identification of a limited number of atypical AEs, nevertheless, broadens the spectrum of potential complications associated with DMTs. Although weaker evidence for causal associations between drug exposure and observed AEs remains a limitation in observational studies without comparable control groups, this study underscores the value of real-world investigations in offering insights into the long-term safety of DMTs, particularly for rare events.